OBITUARY: Emeritus Professor Dr. Dragutin Zelenovic (1928-2020) Founder and Principal Editor of IJIEM (2010-2019) - Marjanovic, Ugljesa (International Journal of Industrial Engineering and Management, 2020)
It is with sincere regret and profound sadness that we announce the passing away of Professor Dragutin Zelenovic on Monday, April 27, 2020. Professor Zelenovic founded the International Journal of Industrial Engineering and Management in 1998 under title Journal of Industrial Systems, which changed the title to the current in 2010 and served as his principal Editor until 2019. Under professor Zelenovic’s direction journal achieved considerable growth, while maintaining a reputation for publishing only the best of Industrial Engineering and Engineering Management research.